Inhaled short‐acting bronchodilators for managing emergency childhood asthma: an overview of reviews. Issue 2 (5th October 2016) - Pollock, M.; Sinha, I. P.; Hartling, L.; Rowe, B. H.; Schreiber, S.; Fernandes, R. M.
Abstract: International guidelines provide conflicting recommendations on how to use bronchodilators to manage childhood acute wheezing conditions in the emergency department (ED), and there is variation within and among countries in how these conditions are managed. This may be reflective of uncertainty about the evidence. This overview of systematic reviews (SRs) aimed to synthesize, appraise, and present all SR evidence on the efficacy and safety of inhaled short‐acting bronchodilators to treat asthma and wheeze exacerbations in children 0–18 years presenting to the ED. Searching, review selection, data extraction and analysis, and quality assessments were conducted using methods recommended by The Cochrane Collaboration. Thirteen SRs containing 56 relevant trials and 5526 patients were included. Results demonstrate the efficacy of short‐acting beta‐agonist (SABA) delivered by metered‐dose inhaler as first‐line therapy for younger and older children (hospital admission decreased by 44% in younger children, and ED length of stay decreased by 33 min in older children). Short‐acting anticholinergic (SAAC) should be added to SABA for older children in severe cases (hospital admission decreased by 27% and 74% when compared to SABA and SAAC alone, respectively). Continuous nebulization, addition of magnesium sulfate to SABA, and levosalbutamol compared to salbutamol cannot be recommended in routine practice.